Transforming haunted heritage into sustainable dark tourism in Central Java - Hussain, Safraz (Central Community Development Journal, 2024)
Dark tourism, which encompasses visits to sites associated with death, tragedy, and supernatural narratives, offers significant yet underdeveloped potential in Central Java’s cultural economy. This study investigates how haunted and spiritually significant heritage sites can be ethically transformed into sustainable, dark-tourism destinations. Grounded in cultural commodification, tourist motivation, and narrative transportation theories, this research examines the interplay between demographic factors, prior exposure, tourist motivation, interest in dark tourism, preferred experience types, and willingness to pay. Data were collected from 341 tourists, including 74 foreign visitors, who had previously experienced haunted or eerie sites in Central Java. Using structural equation modeling (SEM) with SmartPLS 4.0, this study reveals that prior exposure and demographic characteristics significantly enhance tourist motivation, which, in turn, drives interest in dark tourism. Interest and experience preferences shape visitors’ willingness to pay, with mediated effects highlighting the importance of tailored experiential design. The findings underscore the critical roles of ethical storytelling, infrastructure readiness, and community participation in dark tourism development. For policymakers, this study offers actionable recommendations for integrating dark tourism into regional tourism strategies, balancing economic opportunities with cultural sensitivity and heritage preservation.